Impact Of Leadership Behavior On Subordinate - Case Of Japanese Management In Malaysia - NAGASAWA, SATSUKI (2004)
Leadership behavior significantly influences the performance of the companies and the motivation of subordinates. How Malaysian subordinates perceive Japanese expatriates’ leadership behavior, how does it impact on their satisfaction and organizational commitment? To address these questions, this research attempts to investigate the relationship between Japanese expatriates’ leadership behaviors and job satisfaction and organizational commitment of Malaysian subordinates among Japanese companies in Malaysia, and the impact of subordinates’ cultural orientation on this relationship.